BRAND TRUST AND BRAND IMAGE IN SHAPING CONSUMER PURCHASE DECISIONS: A TPB-BASED MEDIATION MODEL OF BRAND LOYALTY - Irawan Yuswono; Juliana Juliana; Sauca Ananda Pranidana (DeReMa (Development Research of Management): Jurnal Manajemen, 2026)
This study investigates the influence of brand trust and brand image on consumer purchase decisions, with brand loyalty serving as a mediating variable, in the context of Fore Coffee, an Indonesian specialty coffee shop brand that offers freshly prepared beverages for immediate consumption (ready-to-drink coffee). Grounded in the Theory of Planned Behavior (TPB), this research explores how attitudinal and control beliefs shape behavioral intentions and actual consumer actions. Using a quantitative approach, data were collected from 193 working consumers across Semarang, Solo, and Yogyakarta, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that both brand trust and brand image significantly influence purchase decisions, both directly and indirectly through brand loyalty. The mediating analysis confirms that brand loyalty partially mediates these relationships, suggesting that emotional commitment reinforces the conversion of brand perceptions into consumer actions. These insights affirm the TPB framework and underscore the importance of cultivating trust and image to foster loyalty and drive purchasing behavior. The study offers practical implications for brand managers and contributes theoretically to consumer behavior literature in emerging digital markets.